Possible Renal Repairing Mechanisms of Mesenchymal Stem Cells in Cyclosporine-Mediated Nephrotoxicity: Endothelial Viability and Hemodynamics - Elshahat Abo-Mosalam Toson; Hanaa Hamdy Ahmed; Hatem Abdel Moneim El-mezayen; Laila Ahmed Rashed; Eslam Samy Elsherbiny (The Indonesian Biomedical Journal, 2019)
BACKGROUND: Stem cell-based therapy may represent the first realistic option for tissue repairing and regeneration. Mesenchymal stem cells (MSCs) are proved to be involved in the regeneration of many tissues which are subjected to different types of injury. Cyclosporine (CsA) in spite of its use as immune suppressive drug during kidney transplantation, it was considered as important model of nephropathy specially, during long-term administration.METHODS: Isolation and preparation of MSCs using Dulbecco's modified Eagle's medium (DMEM), in vitro differentiation through adipogenesis chondrogenesis and osteogenesis was confirmed by using Alizarin Red S stain, Oil Red O stain and Alcian Blue stain, respectively, characterization using flow cytometry technique to detect cluster of differentiation (CD)34, CD44 and CD105 surface markers and homing of MSCs using polymerase chain reaction (PCR) Sry gene assay, were executed. Serum levels of vascular endothelial growth factor (VEGF), endothelin-1 (ET-1) and endothelial nitric oxide synthase (eNOS) were quantified using enzyme-linked immunosorbent assay (ELISA) kits based on the principle of double-antibody sandwich technique. The structural organization of kidney tissue was examined using histological procedures.RESULTS: Single intravenous dose of MSCs is capable to boost kidney repairment process as indicated by the significant decrease in serum ET-1 level paralleled by significant increase in VEGF and eNOS. Moreover, histological findings revealed the improvement of focal hemorrhage in between the degenerated tubules, congestion in the cortical blood vessels, vacuolization in the endothelial cells lining the glomerular tufts and focal perivascular inflammatory cells aggregation.CONCLUSION: This study demonstrated the favorable influence of MSCs in repressing cyclosporine-induced nephropathy in rats. This could be achieved through angiogenic and anti-arteriolopathic mechanisms.KEYWORDS: angiogenesis, cyclosporine, endothelin-1, MSCs, nephropathy